การแสดงเดี่ยวฮอร์นโดย กุลชา แก้วเกตุสัมพันธ์ - กุลชา แก้วเกตุสัมพันธ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
The purpose of this Horn Recital is to study and analyze all pieces chosen for this recital, including the composers’ biography, their inspirations for composing music, and a study of compositions from different periods, to analyze the difference in composition techniques and harmonization between each musical era. For this recital, the performer selects one piece from each period, starting from Baroque until the current period while also including a piece by a Thai composer, to show the difference between the moods, styles, and techniques used in each period. The progression in techniques can be seen clearly from 5 chosen pieces, as follows : (1) Air on the G String by Johann Sebastian Bach (2) Concerto for Two Horns in E-flat Major by Joseph Haydn (3) Concert Piece in F Major for Four Horns by Robert Schumann (4) บทเพลง Andante for Horn and Piano by Richard Strauss (5) Passion by Kitti Kuremanee The Horn Recital will take place on Friday 27th November 2015 at 2:00 p.m. at Siam Yamaha Concert Hall 4th floor, Siam Kolkarn Building (opposite Supatcharasai Stadium), Rama 1 Road. The approximate duration of the recital is one hour.